Efek Ekstrak Daun Binahong (Anredera cordifolia (Ten) Steenis) terhadap Profil Darah Merah pada Marmut (Cavia cobaya) - Dwi Wijayanti; Enny Tantini Setiatin; Edy Kurnianto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
The purpose of this study was to determine the effect of binahong leaves extract (BLE) on Cavia cobaya through the number of erythrocytes, hemoglobin, pack cell volume (PCV) and erythrocyte indices. Complete Random Design (CRD) was used in this study with 4 treatment and 4 replicate, those were T0 (control), T1 (10 mg / head / body weight), T2 (50 mg / head / body weight) and T3 (90 mg / head / weight). The administration of BLE was orally for 10 days pre partum and 10 days postpartum. Blood sampling was done three times, which wasbefore giving BLE , 1 day postpartum and 1 day after the giving of BLE. Data was analyzed using ANOVA and if there was effect of treatment, then continued with Duncan multiple range test. There was not significantly different among treatments for PCV before giving BLE, while the postpartum and post giving BLE showed significantly different (P<0.05). There was not significantl different in the percentage of Hb among treatments for postpartum while in before giving BLE and post giving BLE were showed significantly different (P<0.05). Total erythrocytes was not significantly difference among treatments for before giving BLE while in the postpartum and post giving BLE significantly different (P <0.05). MCHC value was not significantly different between treatments which was before giving BLE and post giving BLE while in the postpartum was showedsignificantly different (P<0.05). MCV and MCH values were not significantly different between treatments before giving BLE while in the postpartum and post giving BLE significantly different (P <0.05). In conclusion, giving BLE at a dose of 50 mg/head/body weight can improve immunity and endurance Cavia cobaya on the treatment group before giving BLE, postpartum and post giving BLE of PCV, Hb, total erythrocytes, MCHC, MCV and MCH.